A Bibliometric Analysis of Hybrid Maize Research using VOSviewer - Taufiq Hidayatullah; Irfan Suliansyah; Etti Swasti; Nurwanita Ekasari Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Corn (Zea mays L.) is one of the most widely cultivated commodities in the world after rice. This study aims to (1) evaluate the most effective database available at Harzing's Publish or Perish software with a year-range search method and the use of additional keywords to obtain the highest number of manuscripts from journal sources relevant to maize hybrids in the field of plant science and agriculture and (2) assess the publication of articles and types of reviews on hybrid maize research related to plant science and agricultural by mapping and visualizing of bibliometric analysis. The data of bibliometric analysis was collected from PubMed, Google Scholar, Semantic Scholar, and CrossRef in Harzing's Publish or Perish software. The keyword used in this research was